An evaluation of the FRIENDS programme: a cognitive behaviour therapy intervention to promote emotional resilience. Issue 10 (27th July 2005) - Stallard, P; Simpson, N; Anderson, S; Carter, T; Osborn, C; Bush, S
Abstract : Aims: To evaluate the efficacy and acceptability of the FRIENDS programme. Methods: Uncontrolled before and after assessment of the FRIENDS programme, a 10 session cognitive behaviour therapy programme. A total of 213 children aged 9–10 years from six primary schools were studied. Main outcome measures: Spence Children's Anxiety Scale, Culture Free Self-Esteem Questionnaire, qualitative assessment of acceptability. Results: End of programme data from 197 children (92.5% of eligible sample) showed significantly lower rates of anxiety (t = 2.95, df = 384) and significantly improved levels of self-esteem (t = 3.13, df = 386). Significant improvements were obtained in over half of those children with the most severe emotional problems. A total of 190 children (89.2%) completed a qualitative assessment of acceptability: 154 (81%) thought it was fun, 147 (77.4%) would recommend it to a friend; 137 (72.8%) thought they had learned new skills, and 78 (41.1%) had helped someone else with their new skills. Conclusions: The FRIENDS programme appears to be an efficacious and acceptable way to promote emotional resilience (reduced anxiety and increased self-esteem) in primary school aged children, consistent with previous studies in Australia. Further controlled studies are needed to assess natural history of anxiety and self-esteem and whether benefits are maintained over time.